Comparison Of Helical And Sequence Techniques On Image Quality In CT Scan Examination Using Water Phantom (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study discusses the comparison of image quality in CT Scan examinations using helical and sequence techniques with a water phantom object. The issue raised is whether these two techniques affect the resulting image quality. The aim of this research is to determine the differences in Signal-to-Noise Ratio (SNR) and Contrast-to-Noise Ratio (CNR) between the helical and sequence techniques. The method used is a quasi-experimental design, where the water phantom is scanned using both techniques with the same parameters, and the results are analyzed using DICOM software. The findings indicate that the sequence technique yields an average SNR of 310.70 and a CNR of 226.25, significantly higher than the helical technique, which reaches only 65.93 and 33.42, respectively. Statistical analysis using the T-Test shows a p-value < 0.05, indicating a significant difference in image quality between the two techniques. In conclusion, the sequence technique is superior in enhancing SNR and CNR image quality in CT Scan examinations, and it is recommended for clinical practice to improve diagnostic accuracy.